2018
DOI: 10.1038/s41467-018-03516-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hoogsteen dynamics on DNA recognition

Abstract: In naked duplex DNA, G–C and A–T Watson-Crick base pairs exist in dynamic equilibrium with their Hoogsteen counterparts. Here, we used nuclear magnetic resonance (NMR) relaxation dispersion and molecular dynamics (MD) simulations to examine how Watson-Crick/Hoogsteen dynamics are modulated upon recognition of duplex DNA by the bisintercalator echinomycin and monointercalator actinomycin D. In both cases, DNA recognition results in the quenching of Hoogsteen dynamics at base pairs involved in intermolecular bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 73 publications
11
75
1
Order By: Relevance
“…The simulated free energy differences and barrier heights are not directly comparable with the experimental results which are estimated based on simple assumption of Boltzmann probability and transition state theory (TST). Still, we obtained the relative free energy of the HG base pair with respect to WC (∆G W C→HG ) to be 4.5 kcal/mol which is within 1 kcal/mol agreement with NMR experiments and microsecond timescale umbrella sampling and meta-dynamics simulations (23,25,26). The positions of the WC and HG minima in χ − Θ space also agree with earlier computational results (25,26).…”
Section: Free Energy Surfaces From Meta-eabfsupporting
confidence: 88%
See 2 more Smart Citations
“…The simulated free energy differences and barrier heights are not directly comparable with the experimental results which are estimated based on simple assumption of Boltzmann probability and transition state theory (TST). Still, we obtained the relative free energy of the HG base pair with respect to WC (∆G W C→HG ) to be 4.5 kcal/mol which is within 1 kcal/mol agreement with NMR experiments and microsecond timescale umbrella sampling and meta-dynamics simulations (23,25,26). The positions of the WC and HG minima in χ − Θ space also agree with earlier computational results (25,26).…”
Section: Free Energy Surfaces From Meta-eabfsupporting
confidence: 88%
“…Enhanced sampling simulation: The newly developed meta-eABF method (39) implemented in NAMD 2.12 through the colvars module (55) has been used to obtain the potential of mean force. The glycosidic angle χ and the pseudo-dihedral angle Θ of the A16-T9 base pair were chosen as order parameters following earlier studies (2,23,26,56). The χ angle denotes torsion of the adenine base with respect to the deoxyribose sugar (defined as the dihedral angle between O4 − C1 − N9 − C4), while the Θ angle captures the flip-out motion of adenine, which leads to extra-helical conformations through base pair breaking (26).…”
Section: System Preparation and Equilibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…an antibiotic with anti-tumor activity (51,52) that binds to CpG steps (CG) in dsDNA. Prior studies have shown that when two echinomycin molecules (or its close analog triostin A) bind to DNA sequences containing a TpA step sandwiched between two CpG bindingsites (d(CGTACG)), the TpA step forms two tandem A-T Hoogsteen bps (25,(53)(54)(55)(56)(57).…”
Section: Echinomycin-dna Complexes As Models For Watson-crick and Hoomentioning
confidence: 99%
“…[2][3][4] Those observations led to a suggestion that the WC double helixes might also code for Hoogsteen base-pairing intrinsically, which offers a way of expanding the genetic information embedded in DNA structures beyond the capacity of WC base-pairing. However, recent NMR studies have observed transient sequence-specific base-pairing other than the WC type, which occurred inside canonical DNA double helixes.…”
mentioning
confidence: 99%